Detecting Insect Pollinator Declines on Regional and Global Scales. Issue 1 (12th December 2012) - Lebuhn, Gretchen; Droege, Sam; Connor, Edward F.; Gemmill‐Herren, Barbara; Potts, Simon G.; Minckley, Robert L.; Griswold, Terry; Jean, Robert; Kula, Emanuel; Roubik, David W.; Cane, Jim; Wright, Karen W.; et al.
Abstract Recently there has been considerable concern about declines in bee communities in agricultural and natural habitats. The value of pollination to agriculture, provided primarily by bees, is >200 billion/year worldwide, and in natural ecosystems it is thought to be even greater. However, no monitoring program exists to accurately detect declines in abundance of insect pollinators; thus, it is difficult to quantify the status of bee communities or estimate the extent of declines. We used data from 11 multiyear studies of bee communities to devise a program to monitor pollinators at regional, national, or international scales. In these studies, 7 different methods for sampling bees were used and bees were sampled on 3 different continents. We estimated that a monitoring program with 200–250 sampling locations each sampled twice over 5 years would provide sufficient power to detect small (2–5%) annual declines in the number of species and in total abundance and would cost U.S.2, 000, 000. To detect declines as small as 1% annually over the same period would require >300 sampling locations. Given the role of pollinators in food security and ecosystem function, we recommend establishment of integrated regional and international monitoring programs to detect changes in pollinator communities. Detección de Declinaciones de Insectos Polinizadores a Escalas Regional y Global